The Templar legacy : [large type] : a novel - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels., 2006)
The ancient order of the Knights Templar possessed untold wealth and absolute power over kings and popes ... until the Inquisition, when they were wiped from the face of the earth, their hidden riches lost. But now two forces, the U.S. Justice Department and a shadowy zealot have learned that it is not at all what they thought it was, and its true nature could change the modern world.